Lexical-semantic group of verbs predictive validity in Ukrainian literary language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article is devoted to the research of verbal lexis of Ukrainian language, where the definite sema ‘observation’ is not actualized, the analyze of semantic category ‘potential observation’, which the regular expression is characteristic of the action verbs.
Keywords: verb; action; sema; category; observation; explication